Academic Supervision For Improving Pedagogical Competence of Classroom Teachers - Fitriyani, Eka Putri; Imam Supardi, Kasmadi; Amin, Yusuf (Educational Management, 2021)
This research aimed to describe and analysis (1) planning of academic supervision for improving pedagogical competence of classroom teachers (2) implementation of academic supervision for improving pedagogical competence of classroom teachers (3) follow up the academic supervision for improving pedagogical competence of classroom teachers. This research is a qualitative research using a case study approach. Data were collected by means of observation, interviews, and documentation. Sources of data, both primary and secondary data, were obtained from three objects, namely persons such as the head of madrasah and teachers, places held at Madrasah Ibtidiyah Negeri Semarang, and papers containing documents about the results of academic supervision. The result of the research includes, (1) planning of academic supervision for improving pedagogical competence of classroom teachers that are (a) before observation (b) during observation, (c) after observation, (d) monitoring. (2) Implementation of academic supervision for improving pedagogical competence of classroom teachers that are (a) monitoring learning administration, (b) monitoring learning practice in classroom. (3) Follow up the academic supervision for improving pedagogical competence of classroom teachers in form of giving awards for the performance done by the teacher.